(untitled) (Bangladesh Journal of Zoology, 2015)
Study has been conducted to establish a suitable culture technique for Tubificid worm, Tubifex tubifex using different culture media. Cowdung, Rawfish and vegetables were evaluated as culture medium. Each medium was supplied as supplementary food at the rate of 250 mg/cm2 per week for 145 days. Water temperature, pH and ammonia of the rearing media ranged from 27.1-31.670C, 5.76-7.35 and 0.5 - <2.5 mg/l respectively. Among the three media, the worms grew well in size in the cowdung medium whereas rawfish showed a moderate growth of worms with remarkable number of new generation of worms. There was no significant growth of worms in the vegetables. The collection of Tubifex was quite difficult but highest amount was in cow dung (8.192 mg/g), moderate in rawfish medium (4.14 mg/g) and lowest in the vegetables (2.43 mg/g). Cowdung medium showed the maximum growth in this study period which is more viable, easy and economical. Bangladesh J. Zool. 42(1): 117-122, 2014